On-Line Temperature Monitoring System of Electrical Equipment Based on Passive Wireless Sensor - Jin Zhu; Yang Yang; Fei Du; Zhiyi Wen; Yongqing Xiao (Journal of Control Science and Engineering)
In order to solve the temperature measurement problem of fully enclosed equipment for power equipment operation inspection, the authors propose an online temperature monitoring system for electrical equipment based on passive wireless sensors. Aiming at the disadvantages of traditional temperature monitoring methods, the system adopts radio frequency technology. The scheme mainly expounds the key technologies and switchgear implementation in the monitoring system research and discusses the feasibility of the system scheme through experiments. Monitor all important components at different times, and establish a temperature monitoring network to complete monitoring and management. According to the test results, in the case of overheating, the temperature can rise to more than 75°C, and the temperature difference measured wirelessly is 0.5°C, which is sufficient to indicate the health of the change. Electrical equipment, the accuracy, and real-time performance of temperature monitoring are guaranteed.